Evaluation of the growth and survival rate of the Caribbean Sea cucumber, Isostichopus badionotus (Selenka, 1867), early juveniles produced in captivity. Issue 4 (30th September 2018) - Sánchez‐Tapia, Itzel A.; Slater, Matthew; Olvera‐Novoa, Miguel A.
Abstract : Isostichopus badionotus is a new commercially important sea cucumber in the Caribbean that has rapidly shown signs of overexploitation. There is no information on the growth and survival rates for wild or hatchery‐produced early juveniles. Hatchery production and determination of juvenile growth rates are essential for future aquaculture efforts for this species. In this study, daily growth rate (GR), specific growth rate (SGR), weight gain (WG), survival rate (SR), and weight–length relation (WLR) were evaluated using small (0.01 g) and large (0.25 g) hatchery‐produced early juveniles under laboratory conditions. Growth was rapid compared to other cultured sea cucumber species; maximal values of SGR and WG were obtained for small juveniles (4.58%/day and 2, 191%, respectively), while maximal GR and SR were obtained for large juveniles (0.29 mm/day and 99.17%, respectively). A wide range of sizes was evident at the end of each trial. The WLR of small and large juveniles fit with a negative allometric growth trend. This study highlights the potential production of I. badionotus as early juvenile stages withstand hatchery handling well and exhibit a high SR, reaching commonly released mean sizes (>0.7 g and 25 mm) after almost 3 months (120 days postfertilization).